Photodegradation and phototoxicity of antibacterial agents and the new alternatives for the photo-inactivation of microorganisms - Vargas, Franklin; Rivas, Carlos; Fernández, Andreína; Flores, Yecira; Padrón, Liliana (Ciencia, 1970)
This review on photodegradation and phototoxicity of antibacterial drugs and new alternatives for photoinactivation of microorganisms takes as model substances of the family of compounds known as quinolonas, which exert their pharmacological activity interacting with the bacterial nucleic acids through a mechanism of intercalation on the DNA. They also pose an adverse phototoxic effect as has been conclusively demonstrated through our investigations in the last 14 years. The studies on two generations of these pharmaceuticals, compounds 1-5 and 6-9 respectively have given positive results regarding photochemical mechanisms of decomposition, intermediates, photoproducts, especially those formed in the presence of oxygen, in such a way as to propose a scale of relative phototoxic activity based on photohemolysis and reactions with human serum albumin (HAS) monitored by means of fluorescence and other spectroscopic technique. Nevertheless those phototoxic undesirable effects, suggests us that those same effects can be reverted for the inactivation of the pathogen agents, provided the appropriate photosensitizer and the luminous sources are used with enough reach to attack them in remote places of the organism where they are. We refer here to lasers directed by means of optic fiber as it is being done in different types of photodynamic therapies. Anyway, this topic continues to be a source of much research.